Recomendações atuais perante pacientes em uso de anticoagulantes ou antiagregantes plaquetários em cirurgia oral - Reis, Augusto Cezar dos Santos (2025)
The growing number of patients undergoing antithrombotic therapy for the prevention and treatment of thromboembolic conditions presents a significant challenge for the performance of oral surgical procedures, as these individuals are at increased risk of developing hemorrhagic and thromboembolic events during the perioperative period. In addition, the variety of available agents has been continuously expanding with the introduction of new drugs to the market. The aim of this study is to synthesize the current evidence regarding the use of anticoagulants and antiplatelet agents in the context of oral surgical procedures. The work was conducted through a literature review using the PubMed and Google Scholar databases, and a total of 20 articles were selected, including clinical studies and literature reviews. The analyzed studies indicate that the risk of bleeding associated with oral surgical procedures in patients on antithrombotic therapy is low, with local hemostatic measures being sufficient to achieve adequate hemorrhage control. It is essential for dental surgeons to have in-depth knowledge of the pharmacology of antithrombotic drugs, as well as of the factors that influence the risk of bleeding and thrombosis, in order to ensure the safe and effective management of these patients.